2019
DOI: 10.20853/33-1-2695
|View full text |Cite
|
Sign up to set email alerts
|

Lecture attendance versus academic performance and prior knowledge of accounting students: An exploratory study at a South African university

Abstract: This study investigates the impact of lecture attendance on first-year Accounting students' academic performance and whether students' prior accounting knowledge differentially benefit from lecture attendance registered or an accounting degree at a South African university. A mixed method was exploited; quantitative, descriptive in nature and fixed effects regression model. Data was collected firstly, from the university's central computer system and from electronic card readers installed in lecture venues. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…This may imply that consistent failing may lead to disgruntlement and discouragement while good academic performance may spark students to put more effort into their school work. These results support the findings of numerous prior studies which reported positive association between lecture attendance and academic performance (Paisey & Paisey, 2004;Clark et al, 2011;LeBlanc, 2005;Nyatanga and Mukorera, 2017;Papageorgiou, 2019).…”
Section: Class Attendance and Demographic Characteristicssupporting
confidence: 91%
See 2 more Smart Citations
“…This may imply that consistent failing may lead to disgruntlement and discouragement while good academic performance may spark students to put more effort into their school work. These results support the findings of numerous prior studies which reported positive association between lecture attendance and academic performance (Paisey & Paisey, 2004;Clark et al, 2011;LeBlanc, 2005;Nyatanga and Mukorera, 2017;Papageorgiou, 2019).…”
Section: Class Attendance and Demographic Characteristicssupporting
confidence: 91%
“…The study by Nyatanga and Mukorera (2017) in South Africa also confirmed a positive and statistically significant relationship between lecture attendance and academic performance among the first and second year students doing microeconomics and macroeconomics modules. Papageorgiou (2019) examined the first year accounting students in South Africa and documented a strong association between lecture attendance and academic performance. Chen and Lin (2008) also reported that lecture attendance affects students' performance and they further reported that students who attended lectures were more likely to improve in their examination performance.…”
Section: Effects Of Class Non-attendancementioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggests that the students experience a positive impact on their academic performance and continuous learning from attending the support classes. This is consistent with literature on attendance of lectures that have found attendance to have a positive influence on academic performance(Van Walbeek 2004;Papageorgiou 2019). This highlights that teaching examination technique methods such as working out questions without a memorandum, under supervised conditions, are perceived as beneficial by the respondents.…”
supporting
confidence: 90%
“…Class participation is a multidimensional concept that comprises many aspects that suggest evidence of student engagement, such as preparation prior to class (Dancer & Kamvounias, 2005;Hard & RaoShah, 2021), attendance (Dancer & Kamvounias, 2005;Fritschner, 2000;Hard & RaoShah, 2021), contribution to class activities and discussions (Dallimore et al, 2010;Dancer & Kamvounias, 2005;Fritschner, 2000;Xu & Qiu, 2020) and frequent small tasks (Tang et al, 2020;Thomlinson et al, 2010). Past research shows that these activities lead to personal and professional growth in students (Jones, 2008), result in a better understanding and retention of the material (Precourt & Gainor, 2019), enable students to demonstrate a broader range of skills (Richardson, 2015) and improve students' performance (Papageorgiou, 2019;Paisey & Paisey, 2004;Precourt & Gainor, 2019). Grading class participation is one of the most popular techniques instructors use to encourage it, as students prioritize graded components in their coursework (Rocca, 2010).…”
Section: Introductionmentioning
confidence: 99%